Microsoft PowerPoint 2013 bible - Wempen, Faithe (Wiley, 2013)
Master PowerPoint and improve your presentation skills with one book! In today's business climate, you need to know PowerPoint inside and out, and that's not all. You also need to be able to make a presentation that makes an impact. From using sophisticated transitions and animation in your PowerPoint presentations to interfacing in person with your audience, this information-packed book helps you succeed. Start creating professional-quality slides that captivate audiences and discover essential tips and techniques for making first-rate presentations, whether you're at a podium or.